Analisis Konsep Ipa-Fisika Sesuai Kurikumum Merdeka Pada Permainan Tradisional Boi - Anatasjia Anatasija Limba; Elsina Sarah Tamaela; Fryan Sopacua; Ledy Manuhutu; ImanuelÂ V. Â Huwae (Postgraduate, University of Mataram, 2023)
An ancient game that has often been played from generation to generation in the Maluku region is the boi game. The boi game can be used as science-physics learning material according to the curriculum in force at school in the hope that it can make the learning process effective and efficient. This research aims to analyze the science-physics concepts found in the traditional Boi game in Allang Village, Leihitu District, Central Maluku Regency, Maluku. The research was conducted using descriptive methods with a qualitative approach. Data collection was carried out through interviews, observations, and document studies. The results of the analysis show that when the player applies force to the ball so that the ball moves and touches the stone structure and/or touches the body of the opposing player, the concepts of kinetic energy, elasticity, momentum, impulse, collision, work, force, and displacement are identified. The position of these concepts in the independent curriculum is at the junior high school phase D and high school phase F